New Economy or Transnational Ownership? The Global Political Economy of Israel - Shimshon Bichler; Jonathan Nitzan (The Bichler and Nitzan Archives, 2002)
An analysis of the political economy of Israel during the 1990s.
Keywords: 330; accumulation; acquisitions; capital; capitalism; centralization; competition; conflict; conglomeration; corporation; credit; crisis; debt; demographics; development; distribution; dual economy; elite; finance; globalization; growth; distribution; inflatio